Surface-Engineered Super-Paramagnetic Iron Oxide Nanoparticles For Chromium Removal - Samrot AV; Sahithya CS; Selvarani A J; Pachiyappan S; Kumar S S (International Journal of Nanomedicine, 2019)
Antony V Samrot,1 Chamarthy Sai Sahithya,2 Jenifer Selvarani A,2 Senthilkumar Pachiyappan,3 Suresh Kumar S4,5 1Department of Biomedical Sciences, Faculty of Medicine and Biomedical Sciences, MAHSA University, Jenjarom, Selangor 42610, Malaysia; 2Department of Biotechnology, School of Bio and Chemical Engineering, Sathyabama Institute of Science and Technology, Chennai, Tamil Nadu 600119, India; 3Department of Chemical Engineering, School of Bio and Chemical Engineering, Sathyabama Institute of Science and Technology, Chennai, Tamil Nadu 600119, India; 4Department of Medical Microbiology and Parasitology, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM), Serdang, Selangor 43400, Malaysia; 5Genetics and Regenerative Medicine Research Centre, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM), Serdang, Selangor 43400, MalaysiaCorrespondence: Antony V SamrotDepartment of Biomedical Sciences, Faculty of Medicine and Biomedical Sciences, MAHSA University, Jenjarom, Selangor 42610, MalaysiaEmail antonysamrot@gmail.comSuresh Kumar SubbiahDepartment of Medical Microbiology and Parasitology, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM), Serdang, Selangor 43400, MalaysiaEmail sureshkudsc@gmail.comBackground: Super-paramagnetic iron oxide nanoparticles (SPIONs) are widely used metal nanoparticles for various applications for its magnetic property and biocompatibility. In recent years, pollution of our environment especially with heavy metals in waterbodies has become a major threat and has left us very minimal sources of freshwater to drink. SPIONs or surface modified SPIONs can be used to remove these heavy metalsMethods: SPIONs were synthesized by co-precipitation method and further coated with a biopolymer, chitosan. Chromium solution was treated with the synthesized SPIONs to study the efficiency of chromium removal by surface adsorption. Later, the adsorption was analysed by direct and indirect analysis methods using UV-VIS spectrophotometry and isotherm studies.Results: Stable chitosan-coated SPIONs were synthesized and they adsorbed chromium better than the uncoated SPIONs, where it was adsorbing up to 100 ppm. Adsorption was found to be increasing with decrease in pH.Conclusion: The surface-modified SPIONs expressed cumulative adsorption action. Even after the adsorption studies, chitosan-coated SPIONs were possessing magnetic property. Thus, the surface-modified SPIONs can become an ideal nanotechnology tool to remove the chromium from groundwater.Keywords: SPIONs, chitosan coating, chromium, adsorption, isotherm studies